Idea univerzity z české perspektivy Rozhovory s Jiřím Hanušem - Balík, Stanislav (Masaryk University Conversations, 2021)
Title in English: The idea of a university from a Czech perspective: Conversations with Jiří Hanuš The aim of this book is to explore the 'idea of a university' and specific modern developments both abroad and in the Czech Republic through dialogues with prominent Czech academics: Stanislav Balík, Petr Dvořák, Petr Fiala, Pavel Floss, Jiří Hanuš, Petr Horák, Jakub Jirsa, Jiří Lach, Jiří Macháček, Tomáš Machula, Dominik Munzar, Ivana Noble, Jan Sokol, Daniel Soukup and Kateřina Šimáčková.